The Language Learning Strategies Used by Students of Merchant Marine Studies Polytechnics Makassar - Nilam Sari Rustam; Arifuddin Hamra; Sukardi Weda (Universitas Negeri Makassar, 2015)
This thesis aims to (1) to investigate the kinds of language learning strategies the merchant marine polytechnics students use in learning English, (2) to investigate the most dominant language learning strategies used by successful and unsuccessful students, and (3) to find out whether or not the successful students employ different language learning strategies from the unsuccessful students. The researcher applied descriptive quantitative method. The population of this research was the students of merchant marine polytechnics of Makassar in academic year 2014/2015. The sample was the fourth semester students of nautical study program, class C which consisted of 30 students. This research used cluster random sampling technique. This research used 2 kinds of instruments; they were English skill tests and questionnaire. The research data was collected by using English skill tests and SILL questionnaire which were analyzed by descriptive and inferential statistic through SPSS 20.0 for windows program.The result of the descriptive quantitative data showed that (1) the nautical students of merchant marine polytechnics used six kinds of language learning strategies namely metacognitive, compensation, social, memory, cognitive, and affective strategy (2) the most dominantly used language learning strategies among the successful students is metacognitive strategy and the most frequently used language learning strategies among unsuccessful students is social strategy (3) there is a difference in using language learning strategies between successful students and unsuccessful students. The six language learning strategies were employed by the students in learning English. The successful students employed two kinds of language learning strategies; metacognitive and compensation strategy while the unsuccessful students employed four kinds of language learning strategies namely social, memory, cognitive, and affective strategy. Keywords: Language Learning Strategies, Successsful/Unsuccessful Students, Metacognitive, Compensation, Social, Memory, Cognitive, And Affective Strategy